2017
DOI: 10.3390/molecules22020224
|View full text |Cite
|
Sign up to set email alerts
|

Antiplasmodial Activity, Cytotoxicity and Structure-Activity Relationship Study of Cyclopeptide Alkaloids

Abstract: Cyclopeptide alkaloids are polyamidic, macrocyclic compounds, containing a 13-, 14-, or 15-membered ring. The ring system consists of a hydroxystyrylamine moiety, an amino acid, and a β-hydroxy amino acid; attached to the ring is a side chain, comprised of one or two more amino acid moieties. In vitro antiplasmodial activity was shown before for several compounds belonging to this class, and in this paper the antiplasmodial and cytotoxic activities of ten more cyclopeptide alkaloids are reported. Combining the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…The plant extracts were assayed against Plasmodium falciparum chloroquine-sensitive (FCB), P. falciparum chloroquine-resistant (W2), and a P. falciparum field isolate (coded CAM06, obtained from local patients) strains using the lactate dehydrogenase (pLDH) method previously described by [22] and modified by [23, 24]. Parasites were cultured in vitro according to the method of [25].…”
Section: Methodsmentioning
confidence: 99%
“…The plant extracts were assayed against Plasmodium falciparum chloroquine-sensitive (FCB), P. falciparum chloroquine-resistant (W2), and a P. falciparum field isolate (coded CAM06, obtained from local patients) strains using the lactate dehydrogenase (pLDH) method previously described by [22] and modified by [23, 24]. Parasites were cultured in vitro according to the method of [25].…”
Section: Methodsmentioning
confidence: 99%
“…Further, two aporphine alkaloids and other compounds were isolated from Xylopia sericea leaves. One of the aporphine alkaloids, anonaine (55)…”
Section: Aporphine and Morphinandienone Alkaloidsmentioning
confidence: 99%
“…e ring system consists of a hydroxystyrylamine moiety, an amino acid, and a β-hydroxy amino acid; attached to the ring is a side chain, comprised of one or two more amino acid moieties [55]. e structures of the cyclopeptide alkaloids from plants that possess antimalarial activity are shown in Figure 10.…”
Section: Protoberberine Alkaloidsmentioning
confidence: 99%
“…Preliminary SAR studies indicated that the 13-membered ring cyclopeptide alkaloids were generally more active than the 14 and 15 membered analogues. Also, a methoxy group on the styrylamine moiety was more favourable for antiplasmodial activity than a hydroxy group [281, 282].…”
Section: Macrocyclesmentioning
confidence: 99%